IKLIM KESELAMATAN KERJA PADA PROYEK KONSTRUKSI DI SURABAYA - Diah Listyaningsih; Feri Harianto (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
One measure of global competition in the construction sector is the low accident rate (zero accident). To realize this, a conducive work safety climate is needed. Work safety climate can be realized needed occupational safety and health management and workforce support. This study aims to evaluate the work safety climate. Sampling was used a purposive sampling method with a work safety climate measurement tool in the form of a questionnaire based on NOSACQ-50 consisting of 7 dimensions, with analysis using a descriptive frequency test, Mann Whitney, and Chi-Square. The results showed that the three projects studied had a good safety climate, besides there were differences in management's safety priorities. The other dimensions, that are the dimensions of developing work safety management, fairness to work safety management, commitment to employee safety, employee safety priorities and the attitude of not wanting to risk work safety, communication and safety training including trusting in peer safety, competence, and worker’s confidence in the work safety system shows that there is no difference. Chi-square test shows that there is no relationship between safety climate with education level, age level and years of service.